Breather, kink and rogue wave solutions of Sharma-Tasso-Olver-like equation - Raheel, M.; İnç, Mustafa; Tala-Tebue, E.; Mahmoud, K. H. (Springer, 2022)
In this paper, we consider the Sharma-Tasso-Olver-Like equation (STOLE) describing the dynamical behaviour of nonlinear dispersive waves in inhomogeneous medium. By using the Hirota bilinear method, some new type of solitons like breather-wave, kink solitary wave and rogue wave, one-, two- and new three-wave solutions to the STOLE have been determined. These results are achieved and verified by using the Maple software. The obtained results are new from the existing results. For the further explanation of these solutions, different kinds of graphs are also drawn. These solitons suggest that this method is effective, straight forward and reliable as compare to other methods.
Keywords: STOLE; Hirota bilinear method; Breather-wave; Kink solitary and rogue wave; One-; two- and three-wave solutions